Influence Equity, Assets and Liabilities to Stock Price With Profitability as an Intervening Variable at PT Bank Syariah Indonesia - Khoirul Anam; Ahmadiono; Abdul Rokhim (Syntax Corporation Indonesia, 2023)
Banks as financial institutions that rely on customer trust are obliged to continually improve service quality in order to maintain their role. In carrying out its business activities, banks have three main functions, including accepting money deposits, lending money, and providing money transfer services. One way to find out the condition of a company can be done by analyzing the annual financial reports made by the company. Financial reports are prepared with the aim of providing an overview of periodic progress reports carried out by the management of the company concerned. This research aims to find out the influence of equity, assets and liabilities on share prices with profitability as an intervening variable at PT Bank Syariah Indonesia in 2020-2022 . Sampling is a part of an overall population that is carefully selected to be representative of that population. The sampling technique used in this research is a time series . The purposive sampling method is the selection of samples that meet certain criteria determined by the researcher. The analysis used uses path analysis using SPSS V22 software. From the results of the data tests in this research, it is clear that equity has an effect on profitability. Assets have no effect on profitability. Liabilities affect profitability. Equity influences share prices. Assets have no effect on share prices. Liabilities affect share prices. Profitability influences share prices. The conclusion of the final hypothesis states that profitability has not been able to partially mediate the influence between equity, assets and liabilities on share prices.